Fine mapping of Glucose 6 Phosphate Dehydrogenase (G6PD) deficiency in rural area of South West Odisha using the clinical, hematological and molecular approach - Ravindra Kumar; MPSS Singh; Soumendu Mahapatra; Sonam Chourasia; Malay Kumar Tripathi; John Oommen; Praveen Kumar Bharti; Rajasubramaniam Shanmugam (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: The aim of the study was to enumerate the clinical, hematological and molecular spectrum of G6PD deficiency in malaria endemic regions of south west Odisha.